Ethics of Verbal Expression and Conduct in the Perspective of Hadith: A Literature Review of Scholarly Publications in Indonesia - Andri Saputra; Azhar Nasution; Rengga Irfan; Arwansyah Bin Kirin (Serambi Madina: Journal of Islamic Studies, 2026)
This study examines scholarly article publications on the theme of ethics of speech and conduct from the perspective of Prophetic hadith. The background of this study highlights the need for a more comprehensive understanding of Islamic moral values that emphasize the importance of guarding one’s speech and improving one’s actions as reflections of faith. The purpose of this research is to analyze the trends, characteristics, and tendencies of academic publications discussing the ethics of speech and conduct from a hadith perspective in Indonesia. The main focus includes mapping publication years, journal accreditation, authors’ institutional affiliations, and the development of research themes. This study employs a qualitative descriptive method with a literature review approach. Data were obtained through a systematic search of scholarly articles using Google Scholar and Dimensions with keywords related to maintaining speech and conduct. A total of 20 relevant articles were analyzed systematically and further mapped using bibliometric analysis assisted by VOSviewer to identify term relationships and thematic trends. The results indicate a significant increase in publications during the 2020–2022 period. In terms of themes, the studies are dominated by legal perspectives, particularly those related to verbal agreements and their juridical implications, followed by cultural themes focusing on oral literature and local wisdom, as well as religious themes addressing the ethics of speech within Islamic and Sufi perspectives. Social, educational, and interdisciplinary themes remain relatively limited. Moreover, only a small number of studies explicitly position hadith as the main object of analysis, while most research still discusses the ethics of speech and conduct in a partial manner. These findings reveal a significant research gap, highlighting the need for the development of more holistic hadith-based studies to strengthen ethical and moral formation in contemporary society.